Transoral robotic surgery and neck dissection alone for head and neck squamous cell carcinoma: Influence of resection margins on oncological outcomes. (July 2022) - Warner, Laura; O'Hara, James T.; Lin, Daniel J.; Oozeer, Nashreen; Fox, Hannah; Meikle, David; Hamilton, David; Iqbal, Muhammad Shahid; Robinson, Max; Paleri, Vinidh
Highlights: Transoral robotic surgery and neck dissection alone for head and neck Squamous cell carcinoma offers 92% local control at 3 years. Provided complete resection is achieved margin dimension did not affect rates of local recurrence. Adjuvant therapy for margin status alone may not convey a survival advantage. Abstract: Objectives: This study reports oncological outcomes of transoral robotic surgery (TORS) and neck dissection (ND) alone for head and neck squamous cell carcinoma (HNSCC) and aims to analyse the influence of resection margins on local recurrence rates. Materials and methods: Fifty-one patients treated with curative intent for HNSCC, with TORS and ND alone between 2013 and 2019 at two tertiary centres were included in this observational multi-centre prospective cohort study. Oncological outcomes are reported on 47 patients for whom the aim was to treat with TORS and ND alone; this excluded four patients who were recommended adjuvant radiotherapy based on resective pathology but did not receive treatment. Local control is the primary endpoint; disease specific, progression free and overall survival are secondary outcomes. Results: With a median follow up of 43 months, estimated outcomes at 3 years (n = 47) were as follows: local control 92%, progression free survival 80%, disease specific survival 94%, and overall survival 84%. Presence of a positive margin on the main specimen was the only statistically significant predictor of local recurrence on univariate Cox regression analysis. Time dependent receiver operating characteristic curve identified margins of 1.1 mm as a threshold for local control, with area under the curve 0.788 (95% CI 0.616–0.960), indicating a good classifier. Conclusion: This is the first UK surgery alone series reporting mature oncological outcomes following TORS and ND. Positive margins on the resected specimen are the strongest predictor of local recurrence, with conventional definitions of "close margins" having no impact.